TEACHING PRESCHOOL DURING COVID-19: THE UTILIZATION OF PLAY-BASED ACTIVITIES IN AN ONLINE SETTING - Yuliana, Marta (Journal of Early Childhood Education (JECE), 2022)
The study aims to showcase the utilization of play-based activities in teaching young learners during Covid-19. During the early stage of the pandemic, all Early Childhood Education (ECE) centers in Indonesia were closed for nearly two years. In July 2020, the Indonesian Ministry of Education and Culture published guidelines for implementing Curriculum under Special Circumstances to support the continuation of the learning process. The guidelines included the recommended educational modules for Early Childhood Learning to help the learning process from home by including activity-based education explanations for teachers, parents, and students. The preschool teachers in Indonesia had to adapt to the new guidelines to continue to educate their students at home. One of the adaptations was to use educational play-kits sent to the students directly to their houses for learning purposes. The method used in this research study is qualitative research through focus-group discussions with the respondents. The study observed 15 preschool teachers from three schools in Jakarta and Pandeglang who utilized play-based activities in their daily lesson plans for two weeks. The finding from the study concluded that play-based activities were effective for early childhood education programs during the pandemic, with solid support from the teachers and parents, sufficient training for the teachers, and a significant variety of activities for the students. In addition, key challenges to overcome in implementing play-based activities in an online setting were teachers' lack of technology-savviness, parents' limited mobile devices, network or connection problems, and budget constraints in developing play-based activities.